1979
DOI: 10.1073/pnas.76.7.3246
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic activity of poly(L-lysine) with some ascites tumor cells.

Abstract: ABSIRACT We have found that poly(L-lysine) can be a very effective agent in preventing the growth of Ehrlich ascites tumors in mice. When given optimal doses of poly(L-lysine) (Mr 60 X 103) intraperitoneally for 5 consecutive days, beginning on day 1 after inoculation with Ehrlich ascites cells, White Swiss mice show nearly a 100% remission from subsequent tumor growth. Rechallenge of "cured" animals with tumor cells, however, shows no long-term immunological protection. In tissue culture, poly(L-lysine) shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 20 publications
(11 reference statements)
8
63
0
Order By: Relevance
“…In pharmaceutical applications poly-L-lysines (PLLs) and poly-Larginines (PLAs) serve as model compounds for the distribution of biologically active substances in organisms and different tissues [7]. It was shown that PLLs and PLAs in high concentrations have anticarcinogenic properties [8]. Cationic polypeptides also serve as models for cell toxic and antimicrobial peptides [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In pharmaceutical applications poly-L-lysines (PLLs) and poly-Larginines (PLAs) serve as model compounds for the distribution of biologically active substances in organisms and different tissues [7]. It was shown that PLLs and PLAs in high concentrations have anticarcinogenic properties [8]. Cationic polypeptides also serve as models for cell toxic and antimicrobial peptides [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The success of the experiments depends on the nature of the polycation used. In the prophylactic model, pLys450 (not shown) was less potent than pLys200, and this result may be a consequence of the more toxic effect detected for pLys of higher molecular weight (12,49). We have shown (12) that pArg720 in a similar concentration transfers peptides more efficiently than did pLys400 and was less toxic.…”
Section: Discussionmentioning
confidence: 76%
“…Arnold et al suggested that poly(Llysine) triggers cellular efflux of organic and inorganic substances proportional to its membrane adsorption. 21) Malik et al demonstrated the membrane interactions of polycations causing erythrocyte lysis. 22) The participation of the protein kinase casein kinase II (CK II) was also discussed, based on observations that in vitro CK II was markedly activated by polycationic structures such as polyamine and spermine.…”
Section: Discussionmentioning
confidence: 99%